Relationship between crude oil price and production levels—An empirical study of OPEC and non-OPEC states - Yang, Tzu-Yi; Chen, Ssu-Han; Yang, Yu-Tai; Chang, Hao-Hsin (Frontiers in Environmental Science, 2022)
This work explores the relationship between the price of crude oil and its production through an empirical study on the regions of the Organization of the Petroleum Exporting Countries (OPEC) and non-Organization of the Petroleum Exporting Countries (non-OPEC). The crude oil price has recently been fluctuating greatly that it cannot be predicted; this fluctuation causes changes in the prices of raw materials for everyday life, thus affecting the economy worldwide. To better understand the factors that affect the crude oil price, this study gathered monthly oil production by OPEC and non-OPEC members, which are divided into the regions of Europe, America, and Asia according to the U.S. Energy Information Administration (2015). Data on the West Texas Intermediate (WTI), Brent, and Dubai oil prices in the period from January 1995 to November 2015 were also gathered and subjected to unbalanced panel random effect regression to investigate the relationship between crude oil price and oil production and to determine whether the oil production by these countries have a significant effect on the fluctuation of crude oil price. This study explored the relationship between production and price, specifically that of crude oil. Hence, it investigated whether and how the changes in monthly crude oil production by OPEC and non-OPEC members in Europe, America, and Asia have affected the changes in three major crude oil prices, namely, WTI, Brent, and Dubai, in the following terms.